KONSEP PENDIDIKAN MULTIKULTURAL SEBAGAI SARANA ALTERNATIF PENCEGAHAN KONFLIK - Yuli Adhani (Sosio-Didaktika: Social Science Education Journal, 2014)
This article provided an overview of the concept of multicultural education as an alternative means of confl ict prevention. The method used to support the writing of this article is the study of literatu re. Point of this article is that multicultural education is a process of developing the full potential of human beingrespectful to plurality and heterogeneity as a consequence of the diversity of culture, ethnicity, religion, economic, social and political background. As one of the world’s biggest multicultural country, Indonesiais supposed deve lop multicultural education as an alternative to prevent social and cultural confl ict that often occurs in Indon esia. In addition build a multicultural society in Indonesia can not be taken for granted by trial and error. On the c ontrary building multicultural society should be pursued in a systematic, programmatic, integrated and sustainabl e. This is because the multicultural reality in Indonesia is an asset that makes Indonesian culturallu very ric h. Therefore, it is necessary for Indonesia to maintain and preserve its rich culture.